Data accompanying A randomised controlled feasibility trial of a BabyWASH household playspace: The CAMPI study - Parker, Alison; Tyrrel, Sean (Cranfield University, 2021)
Water, sanitation and hygiene (WASH) interventions should support infant growth but trial results are inconsistent. Frequently, interventions do not consider behaviours or transmission pathways specific to age. A household playspace (HPS) is one intervention component which may block faecal-oral transmission. This study was a two-armed, parallel-group, randomised, controlled feasibility trial of a HPS in rural Ethiopia. It aimed to recommend proceeding to a definitive trial. Secondary outcomes included effects on infant health, injury prevention and women’s time. Methods. November 2019−January 2020 106 households were identified and assessed for eligibility. Recruited households (N=100) were randomised (blinded prior to the trial start) to intervention or control (both n=50). Outcomes included recruitment, attrition, adherence, and acceptability. Data were collected at baseline, two and four weeks. Findings. Recruitment met a priori criteria (≥80%). There was no loss to follow-up, and no non-use, meeting adherence criteria (both ≤10%). Further, 48.0% (95% CI 33.7−62.6; n=24) of households appropriately used and 56.0% (41.3−70.0; n=28) cleaned the HPS over four weeks, partly meeting adherence criteria (≥50%). For acceptability, 41.0% (31.3−51.3; n=41) of infants were in the HPS during random visits, failing criteria (≥50%). Further, the proportion of HPS use decreased during some activities, failing criteria (no decrease in use). A modified Barrier Analysis described good acceptability and multiple secondary benefits, including on women’s time burden and infant injury prevention. Interpretation. Despite failing some a priori criteria, the trial demonstrated mixed adherence and good acceptability among intervention households. A definitive trial to determine efficacy is warranted if recommended adjustments are made. Includes data, protocols and ethical approval documents.
Keywords: Hygiene'; 'Campylobacter spp'; 'Infant'; 'Fomite'; 'Public Health and Health Services not elsewhere classified'